Decreased CD4 and CD8 Count are Responsible for Severity of COVID-19 Infection (Medical Forum Monthly, 2024)
Objective: The goal of this research was to measure and compare CD4:CD8 ratio in critically ill vs. non-critically ill COVID-19 patients.Study Design: Prospective, and one Pool Cross-sectional Observational study.Place and Duration of Study: This study was conducted at the Pathology department of Rehman Medical Institute (RMI), Peshawar from March 2021 to August 2021.Methods: Peripheral blood samples were taken from 26 critically sick and 26 non-critically sick COVID-19 individuals of comparable age and sex. Absolute WBC count, absolute lymphocyte count, and platelet count were checked and flow cytometry was performed to calculate the absolute CD4 and CD8 T cells counts.Results: The critically ill COVID-19 patients were older (p<0.001) than non-critically sick COVID-19 individuals. In patients who got critically ill, absolute lymphocyte count (p=0.004), absolute CD4 count (p=0.002) and absolute CD8 counts (p=0.014) were low. However, the CD4:CD8 ratio did not differ substantially across the groups (p=0.538). The two groups did not differ in terms of gender.Conclusion: When compared to COVID-19 patients who weren't in critical condition, the absolute lymphocyte count, CD4 count, and CD8 count of critically sick COVID-19 patients were significantly lower. This revealed that the lack of adequate cellular immune responses in critically sick COVID-19 patients may be the cause of the disease severity.